Structural crisis of the capital, machinefacture, and the degradation of work – the social issue in the 21st century - Crise estrutural do capital, maquinofatura e precarização do trabalho - Alves, Giovanni Antonio Pinto (Textos & Contextos (Porto Alegre), 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">We will discuss the new determinations of the degradation of work in the historical conditions of the 21st century. Thus, considering the determinations of the structural value appreciation crisis and the prevalence of machinefacture as a new form of capital production, the degradation of work sets itself not only as wage degradation but also as existential degradation, changing the historical records of the social issue in the 21st century. We will briefly explain the concepts of global capitalism, machinefacture, structural value appreciation crisis, existential degradation, just-in-time way of life, and ideological work.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->